Peningkatan Kapabilitas Karyawan dan Penerapan Budaya Baru Perusahaan dalam Mewujudkan Daya Saing - Sudirlan, Iwan; Maarif, M Syamsul; Affandi, Joko; Arkeman, Yandra (JKBM (JURNAL KONSEP BISNIS DAN MANAJEMEN), 2019)
The rapidly changing world environment requires companies to adjust to existing conditions. Environmental changes that occur include technology, information systems, economic and political causes of the emergence of new regulations and derivatives so that industry and industry players in the implementation can run well. One telecommunication company in Indonesia in maintaining revenue and profit growth improves employee capability and application of new corporate culture in realizing competitiveness. A vision and mission change with complete comprehensive transformation with a strategy embodied in employee-driven programs based on company values. The company in transformation years periode from 2011 until 2016 hold engagement survey with main result the majority of opinions like the changes that occur. Researcher use survey method questionnaires to gather information after reborn launched from Indosat Ooredoo employees as respondents that distributed to a level of staff, managers, division heads and group heads. Descriptive statistical analysis methodology is used to analyze information that has been collected. The results data analysis of the questionnaire showed that 7 (seven) variables assessing the improvement of employee capabilities and the application of the company's new culture in realizing competitiveness showed that the seven variables affected the level of security and comfort of employees and middle management.